Transnational cooperation in times of rapid global changes: The Arctic Council as a success case? - Dorothea Wehrmann (Deutsches Institut für Entwicklungspolitik (DIE), 2020)
Global agreements such as the 2030 Agenda for Sustainable Development and the Paris Climate Agreement illustrate the need for transnational cooperation to solve complex and interrelated challenges that affect humanity at large. But how can transnational cooperation be more successful in times of rapid global changes? This discussion paper shows that many of the premises discussed in the literature on transnational cooperation and on multistakeholder partnerships mirror the praise and concerns brought forward in regard to the Arctic Council as a case of success. At the same time, particularly by advancing its process management, transnational cooperation under the auspices of the Arctic Council could be furthered. This study proceeds as follows. It introduces and compares different approaches in global governance research that are considered as strengthening transnational cooperation and critically explores in how far the Arctic Council can be considered an example to learn from for encouraging transnational cooperation. From the case of the Arctic Council the study further expands on the premises brought forward in the literature and suggests to pay more attention to the dimension of knowledge as particularly in times of rapid global changes a shared understanding of challenges is an important basis for transnational cooperation.
Keywords: 330; Arctic Council; transnational cooperation; institutional success factors; global common good